On the extension of the basic law of laminar flows by means of elliptic integrals - Mikolas, Miklós (Revista Técnica da Faculdade de Engenharia da de Zulia)
A few years ago, the author succeeded in extending the main law of laminar flows to certain more general forms of hoop cross sections, namely by using geometrical and analytical considerations of new type. The present paper deals with the case of elliptical sections for which the theory of elliptic integrals allows of a quite simple integral respresentation and series expansion for the so-called volume stream.